Analisis Perkiraan Kebutuhan Energi Listrik Jangka Panjang Di Propinsi Jawa Tengah Sampai Tahun 2024 Dengan Metode Regresi Linier Berganda - Joko Handoyo (SIMETRIS, 2016)
Electrical energy is a very important energy in life today. Planning needs of electrical energy is also one of the important thingsthat must be considered. The higher the need for electrical energy from year to year, electricity producers must be prepared toavoid the lack of electrical energy. So in the future that the small chance of a crisis of electrical energy needs. To be able to estimatethe electrical energy needs 9 years to 2024 until 2024 will be used multiple linear regression method using the data of the past thatcan be used in predicting the pattern of events in the future. The demand for electrical energy is expected to refer to the electricityneeds of 4 sectors, namely the household sector, the industrial sector, the business sector and the commercial sector. Researchneeds in each sector will be determined using multiple linear regression method with independent variables ie energy needs whilethe independent variables are population, Gross Regional Domestic Product (PDRB), the number of electricity customers and thebasic price of electricity. The result of research of electric energy requirement with multiple linear regression method using visualprogram of basil 2010 gives ease and accelerate calculation to get electric energy requirement, which result obtained in 2016,2017, 2018, 2019, 2020, 2021, 2022, 2023 and 2024 namely 183894 Gwh, 18775 Gwh, 19158 Gwh, 19540 Gwh, 19906 Gwh,20289 Gwh, 20669 Gwh, 21053 Gwh, 21436 Gwh. The significance test obtained from all sectors is Fcount> Ftable, whereas fordetermination coefficient produced by household sector 99%, industrial sector 98%, commercial sector 99% and public sector99%.